Misoprostol as an adjunct to oxytocin can reduce postpartum-haemorrhage: a propensity score-matched retrospective chart review in Bamenda-Cameroon, 2015-2016 - Frederick Morfaw; Mercy Fundoh; Christopher Pisoh; Bi Ayaba; Lawrence Mbuagbaw; Laura N. Anderson; Lehana Thabane (BMC, 2019)
Abstract Background There is some evidence that suggests misoprostol may supplement the action of oxytocin in preventing post-partum haemorrhage (PPH). The primary objective of this study was to determine the effect of the administration of 600 μg misoprostol in addition to oxytocin versus oxytocin alone, on the risk of PPH among pregnant women after delivery. The secondary objectives were to determine the effects of the above combination on maternal death and blood transfusion among pregnant women after delivery; and to determine the incidence of PPH, its case fatality, and the maternal mortality ratio in our hospital. Methods Design and setting: Retrospective chart review of 1736 women delivering at the Regional Hospital Bamenda Cameroon, between 2015 and 2016. This was a pre versus post study following a policy change in the prevention of PPH. Exposure groups: One group received oxytocin-misoprostol (January-April 2016: period after policy change), and the second group received oxytocin-only (January-April 2015: period before policy change) after delivery. Outcomes: The primary outcome was PPH, and the secondary outcomes were maternal death and blood transfusion. Statistical analysis: A 1:1 matching with replacement was done with the propensity score (PS). The groups were compared using PS matching with conditional logistic regression on the matched pairs as the main analysis. A sensitivity analysis was done using other PS adjustment methods and multiple regression. Results Of the 1736 women included in this study, 1238 were matched and compared. Women who received oxytocin-misoprostol were less likely to have PPH as compared to those receiving oxytocin-only (odds ratio [OR] 0.22, 95% confidence interval [CI] 0.08, 0.59, p = 0.003). This reduced odds of PPH was upheld in the different sensitivity analyses. There were no significant differences in the odds of maternal death and the use of blood transfusions between the two groups: OR 3.91, 95% CI [0.44, 35.08], p = 0.22, and OR 0.89, 95% CI [0.14-5.63], p = 0.91, respectively. Sensitivity analyses showed similar results. The incidence of PPH was 2.9% (before adding misoprostol the incidence was 4.4% and after adding misoprostol it was 1.5%), the case fatality rate of PPH was 1.96%, and the overall maternal mortality ratio in the hospital was 293 maternal deaths/100000 life births. Conclusion Our evidence suggests that using 600 μg misoprostol as an add-on to oxytocin in the prevention of post-partum haemorrhage significantly reduces the odds of PPH without affecting other maternal outcomes.